RISK PROTECTION SYSTEM IN THE PROCUREMENT OF SECOND-HAND CARS ACCORDING TO THE MABI’ CONCEPT IN THE BAI’ MUSAWWAMAH CONTRACT - Barizki, T Fariz; Bukhari Ali; Nahara Eriyanti (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
Used car showrooms in Banda Aceh demonstrate that this industry plays an important role in providing more affordable vehicle alternatives for the community. Showrooms such as Nazwa Jaya Mobil and Graha Jaya Mobil offer a wide selection of used vehicles that have undergone rigorous inspections to ensure quality, as well as after-sales services, including warranties and maintenance. With different approaches, these two showrooms have succeeded in attracting consumers by providing high-quality vehicles and flexible financing options. In addition, showroom owners’ ability to assess the condition of used cars suitable for resale is very important for maintaining consumer trust and preventing fraud that can harm both the showroom and the buyer. Furthermore, in terms of risk protection in used car purchase transactions, showroom owners make various efforts to protect their businesses. Measures such as strict supplier selection, vehicle condition checks, clear supplier contracts, and vehicle insurance are part of risk mitigation efforts. In the context of Fiqh Muamalah, the application of the mabī concept in the bai musāwamah contract provides a strong basis for risk protection, emphasising transparency of information, honesty regarding vehicle condition, and the use of written contracts to regulate the rights and obligations of both parties. Thus, the risk protection system applied in used car transactions can minimise losses and increase the sustainability of the showroom business.